Improvement of quality control parameters for the standardization of calotropis procera L. Leaf and flower - ARSHAD AHMAD NAJAR; SWATI KHARE (International Journal of Pharma and Bio Sciences, 2017)
Calotropis procera a key medicinal plant belongs to the family Asclepiadaceae. The macroscopic characters showed that the leaf was alternate, pinnately simple, entire margin, sessile, apex acute etc. The inflorescence possessed lateral and terminal panicles. The leaf showed the presence of open stomata, mesophyll, and vascular bundles etc. While as the flower showed that reproductive part contains anther lobe and 5 petals. The powder microscopy of leaf also revealed epidermal cells, vessels, sclerenchyma cells etc. Flower powder microscopy does not reveal any kind of known structure. Physiochemical analysis of dried leaf powder showed total ash, water soluble ash and acid insoluble ash as 13.44 %, 2.0 % and 0.86% w/w respectively. Preliminary phytochemical screening showed the presence of good amount of flavonoids and alkaloids but steroids were absent. Physiochemical analysis of dried flower powder showed total ash (10.88%)w/w, water soluble ash (1.8% )w/w and acid insoluble ash (0.83% )w/w. Phytochemical screening showed the presence of maximum amount of flavonoids only. The present study was aimed to standardise the pharmacognostic and phytochemical parameters of aerial parts of C. procera. It includes comparative, tissue-specific characterization of the species which provides a significant difference in the drug yields of the two parts (leaf and flower) and would also help in its identification from the sister species of this genus. It has a role in quality production of herbal preparations. In nutshell, the determination of these characters will assist future investigators in the pharmacological analysis of this species.